Peer effect, political competition, and eco-efficiency: Evidence from city-level data in the People's Republic of China - Xudong Chen; Bihong Huang; Yantuan Yu (Asian Development Bank Institute (ADBI), 2020)
This study examines the impacts of political competition on eco-efficiency. We first develop a theoretical model in which local government officials compete against each other to maximize their own political score. We find that after an initial stage of decline, eco-efficiency eventually turns upwards, once environmental performance becomes a meaningful component of local government officials' annual assessment. Eco-efficiency also exhibits a pattern of convergence. Lastly, level of political competition is found to be negatively correlated with eco-efficiency. For the empirical analysis, we use a data envelopment analysis (DEA) model to compute the eco-efficiency level for 191 Chinese cities from 2003 to 2015. Our empirical evidence presents a U-shape pattern in the trend of eco-efficiency, and helps us identify two peer effects that work in opposite directions for cities and regions: the incentivizing effect arising from higher performing neighbors, and the disincentivizing effect when a city outperforms its competitors. Both peer effects lead to convergence in eco-efficiency, and our spatial econometric modeling analysis suggests that the net peer effect is significantly positive. We also find evidence of political competition reducing eco-efficiency, as predicted in the theoretical model. Our findings are robust to alternative measures of eco-efficiency.
Keywords: C61; C67; Q56; R15; 330; peer effect; political competition; eco-efficiency; spatial analysis; People's Republic of China